2021
DOI: 10.3390/ijms22158046
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Neutrophil Extracellular Traps (NETs) from Cow, Sheep and Goat Models

Abstract: This review provides insight into the importance of understanding NETosis in cows, sheep, and goats in light of the importance to their health, welfare and use as animal models. Neutrophils are essential to innate immunity, pathogen infection, and inflammatory diseases. The relevance of NETosis as a conserved innate immune response mechanism and the translational implications for public health are presented. Increased understanding of NETosis in ruminants will contribute to the prediction of pathologies and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 156 publications
0
11
0
Order By: Relevance
“…Interestingly, the formation of NETs is always accompanied by reactive oxygen species (ROS) production, and therefore, ROS may be an indirect way to evaluate the production of NETs in vitro. Moreover, the production NETs and ROS can be considered potential indicators or biomarkers to monitor (metabolic) inflammation and immunosuppression [ 14 ]. Though, it is not fully elucidated yet whether the capacity to produce NETs and ROS by circulating PMN is different in dairy cows during the transition phase in comparison to other periods in the lactation cycle or even in nulliparous heifers.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the formation of NETs is always accompanied by reactive oxygen species (ROS) production, and therefore, ROS may be an indirect way to evaluate the production of NETs in vitro. Moreover, the production NETs and ROS can be considered potential indicators or biomarkers to monitor (metabolic) inflammation and immunosuppression [ 14 ]. Though, it is not fully elucidated yet whether the capacity to produce NETs and ROS by circulating PMN is different in dairy cows during the transition phase in comparison to other periods in the lactation cycle or even in nulliparous heifers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that most mammary pathogenic bacteria could induce NETosis ( 19 ). Such as E. coli , Staphylococcus aureus ( S. aureus ) and Klebsiella pneumoniae ( 19 ). Pisanu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that most mammary pathogenic bacteria could induce NETosis (19). Such as E. coli, Staphylococcus aureus (S. aureus) and Klebsiella pneumoniae (19). Pisanu et al detected NETs in the mammary gland alveoli and milk from S. uberis-infected sheep (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, NETosis has not been studied in Babesia infections [ 12 , 226 , 227 , 228 , 229 , 230 , 276 ]. Activation of neutrophils and release of NETs have been observed in various human parasitic infections, including malaria, leishmaniosis, onchocerciasis (induced by endosymbionts Wolbachia ), and toxoplasmosis, as well as in bacterial, fungal, and viral infections, in experimental animal models, in in vitro experiments, and in dogs with sepsis [ 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 ]. It seems probable that similar mechanisms to those observed in malaria are involved in sequestration of RBCs in babesiosis.…”
Section: Sequestration Of Rbcsmentioning
confidence: 99%